Gene expression of NMDA and AMPA receptors in different facial motor neurons. (7th September 2015) - Chen, Pei; Song, Jun; Luo, Linghui; Cheng, Qing; Xiao, Hongjun; Gong, Shusheng
Abstract : Objectives/Hypothesis: Facial motor neurons (FMNs) are involved in the remodeling of the facial nucleus in response to peripheral injury. This study aimed to examine the gene expression of alpha‐amino‐3‐hydroxy‐5‐methylisoxazole‐4‐propionic acid receptor (AMPAR) and N‐methyl‐D‐aspartate subtype of ionotropic glutamate receptor (NMDAR) in reinnervating dormant FMNs after facial nerve axotomy. Study Design: Animal study. Methods: Rat models of facial‐facial anastomosis were set up and raised until the 90th day. By laser capture microdissection (LCM), the reinnervating neurons labeled by Fluoro‐Ruby (FR) were first captured, and the remaining (dormant) neurons identified by Nissl staining were captured in the facial nucleus of the operated side. The total RNA of two types of neurons were extracted, and the gene expressions of AMPAR and NMDAR were studied by real‐time quantitative reverse‐transcriptase polymerase chain reaction (qRT‐PCR). Results: Messenger RNA (mRNA) of AMPAR subunits (GluR1, GluR2, GluR3, and GluR4) and NMDAR subunits (NR1, NR2a, NR2b, NR2c, and NR2d) was detected in reinnervating and dormant neurons. The relative ratios exhibited that the expressions of GluR1, GluR4, NR2a, NR2b, NR2c, and NR2d mRNA were lower, whereas the expressions of GluR2, GluR3, and NR1 mRNA were higher in dormant FMNs than in reinnervating counterparts. Conclusions: LCM in combination with real‐time qRT‐PCR can be employed for the examination of gene expression of different FMNs in a heterogeneous nucleus. The adaptive changes in AMPAR and NMDAR subunit mRNA might dictate the regenerative fate of FMNs in response to the peripheral axotomy and thereby play a unique role in the pathogenesis of facial nerve injury and regeneration. Level of Evidence: NA Laryngoscope, 126:E6–E11, 2016